(4+x)(6+x)=48

Simple and best practice solution for (4+x)(6+x)=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4+x)(6+x)=48 equation:



(4+x)(6+x)=48
We move all terms to the left:
(4+x)(6+x)-(48)=0
We add all the numbers together, and all the variables
(x+4)(x+6)-48=0
We multiply parentheses ..
(+x^2+6x+4x+24)-48=0
We get rid of parentheses
x^2+6x+4x+24-48=0
We add all the numbers together, and all the variables
x^2+10x-24=0
a = 1; b = 10; c = -24;
Δ = b2-4ac
Δ = 102-4·1·(-24)
Δ = 196
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{196}=14$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(10)-14}{2*1}=\frac{-24}{2} =-12 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(10)+14}{2*1}=\frac{4}{2} =2 $

See similar equations:

| 4m+4(4m+2)=108 | | 15+m=12 | | -10=w-3 | | -6=-5/9+b | | 41​ z−72​ =75​ | | 0.36y+0.18y=2.1-0.16 | | 4x+3(6+x)-1=2 | | 6x29=5 | | 1/4=x/11 | | -6=45+b | | 8x-1=5x+38 | | 5/(5+5^(-0.005x))=0.96 | | p−2=7 | | (2y-7)+8(y+6)=31 | | 0=-(x-4)^2 | | 3z/10+1=9 | | 6(x+9=36 | | 5(x+5)+2x=3(2x+1)+2 | | P+3/w=(-1) | | 3(4x-18)-3x=-36 | | 9x+107x=5(x+2 | | 9x+107x=5(x+2 | | X-(40-x)=14 | | 2(2y+12)-3y=22 | | 8x5=5(x4) | | 7.1+2x=11.1 | | 6(2x+1)=3(x4) | | 5/6x−2=−2/3x+1 | | 16=k÷1+ | | 10=-c+3 | | -8n+4=-7n+7 | | 2(5x-31)-5x=-22 |

Equations solver categories